Profile of thoracic injury at College of Medical Sciences Teaching Hospital - Chapagain, D; Reddy, D Jayapal; Shah, S; Shrestha, KG (Journal of College of Medical Sciences-Nepal, 2014)
Objectives: Thoracic injury is a challenge to the thoracic surgeon practicing in developing countries. This prospective study was conducted to see the mode of injury, injury types and overall outcome of thoracic injury in our settings. Materials and methods: This prospective study was conducted in 100 thoracic injury patients between December 2011 to June 2012. The demographic features, type of the trauma, radiological assessment, associated organ injuries, management of the injury, surgical interventions, morbidity, mortality, length of hospital stay were analysed. Results: In this study the ages ranged from 7 to 84 years. There were 73 (73%) males and 27 (27%) females. The majority of patients (83%) were injured during the evening and night time. The majority of patients 92(92%) sustained blunt chest injuries. The mechanism of injury was not significantly associated with length of hospital stay (P > 0.05) and mortality (P > 0.05).Road traffic accident was the most common cause of injuries affecting 68(68%) of patients followed by fall injury of 19(19%). Rib fractures, haemothorax, pneumothorax and lung contusion were the most common type of injuries accounting for 83.0%, 57%,34% and 33% respectively. Associated extra-thoracic injuries were noted in 64.0% of patients. 45(45%) of the cases of haemothorax, pneumotharax and haemopneumothorax were treated by tube thoracotomy. Four patients (04%) had undergone thoracotomy. There were 09(09%) patients of flail chest and treated conservatively. Fourty six patients (46%) were admitted in the ICU. Eleven (11%) patients were treated with ventilator support. Seventeen (17%) patients had complication. The overall length of hospital stay ranged from 0 to 25 days. Conclusion: Road traffic accidents and fall from height are the major public health problems. Preventive measures at reducing road traffic accidents and timely management with closed tube thoracotomy are the main factors to be considered in the thoracic injury. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 30-39 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9671